Fast and Furious: Ethylene-Triggered Changes in the Metabolism of Papaya Fruit During Ripening - Fabi, João Paulo; do Prado, Samira Bernardino Ramos (Frontiers in Plant Science, 2019)
Papaya is a climacteric fleshy fruit characterized by a fast ripening after harvest. During the relatively short postharvest period, papaya fruit undergoes several changes in metabolism that result in pulp softening and sweetening, as well as the development of a characteristic aroma. Since papaya is one of the most cultivated and appreciated tropical fruit crops worldwide, extensive research has been conducted to not only understand the formation of the quality and nutritional attributes of ripe fruit but also to develop methods for controlling the ripening process. However, most strategies to postpone papaya ripening, and therefore to increase shelf life, have failed to maintain fruit quality. Ethylene blockage precludes carotenoid biosynthesis, while cold storage can induce chilling injury and negatively affect the volatile profile of papaya. As a climacteric fruit, the fast ripening of papaya is triggered by ethylene biosynthesis. The generation of the climacteric ethylene positive feedback loop is elicited by the expression of a specific transcription factor that leads to an up-regulation of 1-aminocyclopropane-1-carboxylic acid (ACC) synthase (ACS) and ACC-oxidase (ACO) expression, triggering the system II ethylene biosynthesis. The ethylene burst occurs about three to four days after harvest and induces pectinase expression. The disassembling of the papaya cell wall appears to help in fruit sweetness, while glucose and fructose are also produced by acidic invertases. The increase in ethylene production also results in carotenoid accumulation due to the induction of cyclases and hydroxylases, leading to yellow and red/orange colored pulp phenotypes. Moreover, the production of volatile terpene linalool, an important biological marker for papaya sensorial quality, is also induced by ethylene. All these mentioned processes are related to papaya sensorial and nutritional quality. We describe the understanding of ethylene-triggered events that influence papaya quality and nutritional traits, as those characteristics are a consequence of an accelerated metabolism during fruit ripening.